2010
DOI: 10.3348/kjr.2010.11.6.632
|View full text |Cite
|
Sign up to set email alerts
|

Value of Power Doppler and Gray-Scale US in the Diagnosis of Carpal Tunnel Syndrome: Contribution of Cross-Sectional Area just before the Tunnel Inlet as Compared with the Cross-Sectional Area at the Tunnel

Abstract: ObjectiveTo determine the value of gray-scale and power Doppler ultrasonography in the evaluation of carpal tunnel syndrome (CTS).Materials and MethodsMedian nerves at the carpal tunnel were evaluated by using gray-scale and power Doppler ultrasonography and by using accepted and new criteria in 42 patients with CTS (62 wrists) confirmed by electromyogram and 33 control subjects. We evaluated the cross-sectional area of the nerve just proximal to the tunnel inlet (CSAa), and at mid level (CSAb). We then calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
91
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(95 citation statements)
references
References 25 publications
3
91
0
1
Order By: Relevance
“…In this study, a logical occasion that CTS present in mean age of (41.5 ± 6.5) years agrees with other researchers as Phalen [25] who reported that the peak age range of patients with CTS was 40–60 years [26] and Akcar et al [4] who studied a sample with ages ranging between 33 and 58 years.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, a logical occasion that CTS present in mean age of (41.5 ± 6.5) years agrees with other researchers as Phalen [25] who reported that the peak age range of patients with CTS was 40–60 years [26] and Akcar et al [4] who studied a sample with ages ranging between 33 and 58 years.…”
Section: Discussionsupporting
confidence: 91%
“…It accounts for 90% of all entrapment neuropathies [3] and it is particularly prevalent in middle-aged women [4] and is recognized as one of the most important causes of the workplace morbidity [5]. The prevalence of CTS in the United Kingdom was 7–16% in 2010, while in the United States was only 5% [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no protocol for obtaining these waveforms was provided, and no criterion was reported to ensure that blood flow measurements using Doppler were taken within the median nerve instead of in the surrounding tissues. Mallouhi et al 9 and Akcar et al 16 successfully collected Doppler tracings within the carpal tunnel; however, these study reports lacked the detail necessary to replicate their results. The present study provides a detailed methodology for recording blood flow using Doppler, as well as a rigorous process for evaluating the validity of the waveforms for statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…19 Power Doppler ultrasound is considered superior to colour Doppler in demonstration of vascular flow due to high sensitivity to slow flow, no angle dependency, and no aliasing. 20 Malhoui et al used colour Doppler for evaluation of hypervascularity of non-bifid median nerve and found that it has a good sensitivity and specificity for diagnosing CTS.…”
Section: -11mentioning
confidence: 99%